Noise cancellation: disrupting audio perception. (1st January 2013) - Simpson, Cara-Ann; Cheng, Eva
Noise cancellation: disrupting audio perception is an interactive sound and visual art installation that explores the creation of new technology – open-air active signal cancellation – and how it can be incorporated into interactive art installations. As an ongoing collaborative project between artist and engineer, noise cancellation engages signal processing research issues in a creative application space. This paper describes the collaborative installation work in progress and discusses why this active signal cancellation technology is important in relation to changing modes of listening and hearing, altering spatial perception and encouraging audiences to fully interact with art installations within art galleries (and related spaces).